The spectrum on prism graph using circulant matrix - Triyani, Triyani; Mashuri, Mashuri; Anarkis, Bunga Tirai; Riyadi, Slamet (Bulletin of Applied Mathematics and Mathematics Education, 2022)
Spectral graph theory discusses about the algebraic properties of graphs based on the spectrum of a graph. This article investigated the spectrum of prism graph. The method used in this research is the circulant matrix. The results showed that prism graph P2,s is a regular graph of degree 3, for s odd and s ≥ 3, P2,s is a circulantt graph with regular spectrum.